A Study of Extra Biliary Complications of Laparoscopic Cholecytectomy - Ullah, A Z M Forman; Karim, Mohammed Masud; Haque, Syed Aminul; Rahman, Tanvir; Siddique, Ashiqur Rahaman; Jannat, Tahmina; Begum, Jasmin (IAHS Medical Journal, 2023)
Background: Laparoscopic cholecystectomy has rapidly become the procedure of choice for gallbladder removal and has become the most common major abdominal procedure performed throughout the world. To observe the extrabiliary complications of laparoscopic cholecystectomy this research work was done. Materials and methods: This observational study was carried out in the Department of Surgery, Chittagong Medical College Hospital, Chattogram, duration December 2015 to November 2016. A total of 100 Gall stone diseased patients were enrolled in this study and they were randomly allocated. Post operatively patients were observed, Data were collected, and Statistical analysis were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-22). Results: Among 100 patients male to female ratio was 4.6:1 with maximum age group of third and fourth decade. Seventeen patients were associated with other disease e.g. diabetes mellitus and hypertension. Per-operative complication rate was 5(5.0%) among those, per-operative port site bleeding 2(2.0%), cystic artery bleeding 1(1.0%), liver bed bleeding was in 2(2.0%) cases. All these complications were managed successfully and smooth recovery within normal time.Post-operative complication rate was 1(1.0%). Among those port sites infection were in 1(1.0%) case. Conclusion: The findings of this study are expected to help taking perioperative measure to prevent extra-biliary complications. There may be some other devastating complications which may cripple the patients as well as surgeon. IAHS Medical Journal Vol 5(1), June 2022; 45-48